Advanced computer model for analysis of reinforced concrete and composite structures at elevated temperatures - Neves,Natan Sian das (2021)
abstract: This paper is concerned on the development of a computational model based on finite element procedures for advanced analysis capable of estimating the behavior of reinforced concrete and composite steel-concrete plane structures exposed to fire. The program implemented is called NASEN, the specific thermo-structural module is used to analyze structures under fire conditions. The effects of geometric nonlinearity, material nonlinearity and nonlinear thermal gradients are incorporated into the model, as well as the degradation of material properties with increased temperature. The methodology applied for the solution is based on the unidirectional coupling of the thermal and mechanical solutions. The cross-sections of the structural elements are discretized with two-dimensional meshes for thermal analysis, while the structural analysis uses a one-dimensional beam-column element. Numerical examples are presented to demonstrate the accuracy of the computational code developed in relation to the numerical and experimental solutions found in the literature. In summary, the program adequately predicted the response of the studied structures.